Culture as Dialogue - Węcławiak, Alicja (Journal of Applied Cultural Studies, 2016)
The aim of the study is to demonstrate the paradoxicality determining human life. The natural aspiration of the subject is to strive to achieve order, enabling a reasonably satisfying and passably predictable life, guaranteeing the essential sense of security both on an individual and on a social dimension. The ancient writers and thinkers saw the origins of differentiation, and thereby of the impossibility of achieving coherence and order, in the external reality. Views of thinkers of the 19th and 20th centuries show not only a demand for diversity to be taken into consideration, but also reveal their picture of culture as something highly heterogeneous that cannot be reduced to just a single, preferred vision. Multitude of models and values creates the potential for dialogue, which is irregular and spontaneous.